Human and Murine Evidence for Mechanisms Driving Autoimmune Photosensitivity - Wolf, Sonya J.; Estadt, Shannon N.; Gudjonsson, Johann E.; Kahlenberg, J. Michelle (Frontiers in Immunology, 2018)
Ultraviolet (UV) light is an important environmental trigger for systemic lupus erythematosus (SLE) patients, yet the mechanisms by which UV light impacts disease are not fully known. This review covers evidence in both human and murine systems for the impacts of UV light on DNA damage, apoptosis, autoantigen exposure, cytokine production, inflammatory cell recruitment, and systemic- flare induction. In addition, the role of the circadian clock is discussed. Evidence is compared in healthy individuals and SLE patients as well as in wild-type and lupus-prone mice. Further research is needed into the effects of UV light on cutaneous and systemic immune responses to understand how to prevent UV-light mediated lupus flares.